Prevalence of HIV infection in patients hospitalized for tuberculosis in Bahia, Brazil - Matos,Eliana Dias (2007)
HIV infection is an important risk factor for the development of tuberculosis (TB), and also affects its morbidity and mortality. This study estimated the prevalence of HIV infection in patients hospitalized for TB in Bahia (in northeastern Brazil) and to evaluate its impact on in-hospital mortality. A total of 375 patients with TB, admitted consecutively to a TB reference hospital in Salvador (Bahia, Brazil), were evaluated between July 2001 and July 2003. Anti-HIV serology was performed in all patients irrespective of clinical and/or epidemiological data suggestive of HIV infection. Death during hospitalization was the principal event-dependent variable. Mean age of patients was 41.4 ± 16.2 years and the male/female ratio was 3.4:1.0. The prevalence of HIV infection was 8.8% (95%CI: 6.2-12.0%). Patients in the HIV-positive group were younger than those in the HIV-negative group (37.1 versus 41.9 years; p=0.05). In-hospital mortality was 10.9% for the whole group (95%CI: 9.4-15.9%), but was significantly greater in the HIV-positive group compared to the HIV-negative group (27.3% versus 9.4%; RR=2.9; 95%CI: 1.5-5.6; p=0.002). The prevalence of HIV infection in patients hospitalized for TB in Bahia (northeastern Brazil) is relatively high (8.8%) and mortality is significantly higher (2.9-fold) in the HIV-positive group. These findings justify carrying out HIV testing, as recommended by the Brazilian Ministry of Health, in all TB patients, particularly those requiring hospitalization.